Practical Apache Struts2 Web 2.0 Projects - Roughley, Ian (Springer, 2017)
Apache Struts has long provided Java developers with a powerful framework for building extensible, maintainable web applications. Yet the version 2 release takes developers' capabilities to the next level, having integrated Ajax support, the ability to easily integration with the Spring framework, and the ability to take full advantage of POJOs. Practical Apache Struts 2 Web 2.0 Projects shows you how to capitalize upon these features to build next–generation web applications that both enthrall and empower your users.